The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3892/or.18.1.105
|View full text |Cite
|
Sign up to set email alerts
|

RARβ2 suppression in head and neck squamous cell carcinoma correlates with site, histology and age

Abstract: Abstract. Retinoids as important growth and differentiation regulating agents have a potential role in the chemoprevention of head and neck squamous cell carcinoma (HNSCC). Despite the promising preclinical and early clinical findings, limitations of application are raised by intrinsic resistance acquired during carcinogenesis. Retinoic acid receptor ß2 (RARß2) is one of the proximate mediators of retinoid signalling and its expression is often diminished in early stages of head and neck carcinogenesis. One fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…furthermore, the prevalence was reported to increase with a higher grade of dysplasia (23). olazs et al (31), among others, analyzed the effects of hypermethylation and loss of heterogeneity in genes that transcribe rArβ 2 receptors, studying their role in retinoid therapy and chemoprevention. In their study of 89 primary head and neck tumours, methylation was the major cause of suppression of these receptors and was found in the tumour and as an early event in the carcinogenesis.…”
Section: Rarβ 2 (Retinoic Acid Receptor)mentioning
confidence: 99%
See 2 more Smart Citations
“…furthermore, the prevalence was reported to increase with a higher grade of dysplasia (23). olazs et al (31), among others, analyzed the effects of hypermethylation and loss of heterogeneity in genes that transcribe rArβ 2 receptors, studying their role in retinoid therapy and chemoprevention. In their study of 89 primary head and neck tumours, methylation was the major cause of suppression of these receptors and was found in the tumour and as an early event in the carcinogenesis.…”
Section: Rarβ 2 (Retinoic Acid Receptor)mentioning
confidence: 99%
“…In their study of 89 primary head and neck tumours, methylation was the major cause of suppression of these receptors and was found in the tumour and as an early event in the carcinogenesis. rArβ 2 methylation was not associated with tumour localization, stage or metastasis but was related to higher age, apparently due to the longer contact time between carcinogenic elements and mucosa (31). It also appears to be significantly related to tumours with an aggressive phenotype and to a poor survival prognosis (29).…”
Section: Rarβ 2 (Retinoic Acid Receptor)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Smigiel et al (17), CDKN2A hypermethylation is reflected by a high grade of histological differentiation of the tumor (G3) (17). Olasz et al (18) reported that RARβ2 hypermethylation is observed in patients with well-differentiated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Improper methylation status of the following genes has been identified thus far in laryngeal cancer: Retinoic acid receptor β (RARβ), death-associated protein kinase (DAPK), cyclin-dependent kinase inhibitor 2A (CDKN2A), MGMT, RASSF1A, fragile histidine triad, chromodomain-helicase-DNA-binding protein 5, cellular retinol binding protein 1 and HIC1 (12)(13)(14)(15)(16)(17)(18)(19). The majority of the studies reported certain correlations between the clinical course of the disease and the molecular changes identified.…”
Section: Discussionmentioning
confidence: 99%